«The Three Seas Initiative»: Perspectives of Energy Sector Development within the Croatian Foreign Policy - M. Zubovic (Проблемы постсоветского пространства)
The article revolves around the Three Seas Initiative, a project launched in 2015 by the Republic of Croatia and the Republic of Poland, aimed at the development of cooperation and international relations between its 12 member states in the sphere of energy, digitalization and transport. Special emphasis is put on the development of Croatia’s foreign policy in the energy sector within the aforementioned Initiative, which can be achieved through the country’s participation in the construction of an LNG terminal on the island of Krk in Croatia. Moreover, both positive and negative aspects of the Initiative are presented in the article, considering the fact it has attracted not only the attention of western EU countries, but also the United States and Russia. Croatia’s participation in the projects of the Three Seas Initiative as one of its founders is considered to be one of the biggest steps in the country’s recent foreign policy, and if successfully put into practice, the Initiative could provide Croatia an opportunity to strengthen its geopolitical position in Europe.